Conflict of interest: law enforcement and conflictology - N. A. Bobrova (Правоприменение, 2022)
The subject. The article is devoted to conflictology as one of the most relevant, almost significant, debatable problems in law theory, legal sciences, political science, philosophy, psychology and economics. The author analyzes specific examples of conflicts of interest in various corruption spheres and manifestations, for example, in the sphere of participation of economic actors in the procurement announced by state and municipal authorities.The purpose of the article is to identify the nature of conflicts of interest as the basis of corruption.The methodology. The author uses comparisons of common and private, cause and effect, patterns and randomness, content and form, essence and phenomenon, the transition of quantity into quality, as well as the methods of sociology and psychology.The main results, scope of application. The article analyzes the relationship between corruption and nepotism. The article discusses legal and moral ways to prevent conflict, the role of ethical standards in conflict prevention, regulatory framework for preventing and settling them, the ratio of conflict of interest and employee qualifications, balance of material and personal interest, Commissions to prevent conflicts of interest, guaranteeing the role of writing notice of a conflict of interest, Features of the notification procedure, moral means of preventing and resolve conflicts of interest. Exclusively legal methods are insufficient to prevent and eliminate conflicts of interest and corruption-related risks. A combination of legal and moral measures is necessary, and most importantly, the exclusion of kinship and other forms of nepotism in the formation of government bodies and the appointment of officials, the hiring of state and municipal employees. It is necessary to exclude formalism from the institution of competitive selection of civil servants.Conclusions. The elimination of the contradictions between some federal anti-corruption laws has much less effect on the state of corruption in the state than the flourishing nepotism. The exercise of official functions takes place in the form of law enforcement: if there is no application of the law – there is no corruption. The main emphasis should be directed to the process of forming the apparatus of state and municipal authorities, employees of state and municipal institutions, primarily in the educational sphere, on which the upbringing of new generations of employees depends, the steady observance of high professional and moral requirements imposed on state and municipal employees and teachers in schools and universities.